2018
DOI: 10.1002/ece3.3784
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont‐conferred reproduction and fitness benefits can favour their host occurrence

Abstract: Double infections of Wolbachia and Spiroplasma are frequent in natural populations of Tetranychus truncatus, a polyphagous mite species that has been a dominant species in China since 2009. However, little is known about the causes and ecological importance of such coexistences. In this study, we established T. truncatus strains with different infection types and then inferred the impact of the two endosymbionts on host reproduction and fitness. Double infection induced cytoplasmic incompatibility, which was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
(66 reference statements)
2
30
0
Order By: Relevance
“…In our previous study (Zhang et al ., ), we found that the spider mites doubly infected with Wolbachia and Spiroplasma have reproductive and fitness advantages, like higher egg deposition and faster developmental rate, compared with singly infected and uninfected spider mite strains. Doubly infected mites could induce incomplete CI, whereas Wolbachia singly infected mites could not induce CI.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In our previous study (Zhang et al ., ), we found that the spider mites doubly infected with Wolbachia and Spiroplasma have reproductive and fitness advantages, like higher egg deposition and faster developmental rate, compared with singly infected and uninfected spider mite strains. Doubly infected mites could induce incomplete CI, whereas Wolbachia singly infected mites could not induce CI.…”
Section: Discussionmentioning
confidence: 67%
“…). These results were similar to those found in our former study (Zhang et al ., ). There was no direct association between CI and Wolbachia density, with Wolbachia density significantly higher in 1‐day‐old male adults from the co‐infected strain (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Yun et al (2013) and Zhang, Yang, Zhu, and Hong (2018) assessed Wolbachia as endosymbiotic bacteria that induce beneficial effect in spiders' growth and development process; this beneficial association was helpful in regulation of biological traits in spiders. Furthermore, a nonsignificant relationship was found between the total survival rate and Wolbachia infection in H. graminicola.…”
Section: Discussionmentioning
confidence: 99%